Exploring the influence of service quality (sq) on patient satisfaction (ps) : a case study of universiti malaysia pahang health centre (umphc) - Khairul Salleh, Abdul Basit (2022)
The patient satisfaction and healthcare service quality has been studied for ages. The primary care centre’s such as UMP Health Centre (UMPHC) are the intermediaries between patients and hospital referral. Hence, they have the most contact and influence on customers because they are convenient, strategic and become the primary direct contact with patients on a daily basis, especially the university community. As the health care organizations are trying to improve their return on investment, UMPHC has started to implement steps in curbing the patient dissatisfaction issues with the study of service quality and patient satisfaction. In this paper, the author looks into the dimensions of service quality that influence patient satisfaction in their visits and appointments at UMPHC. The impact of various service quality’s dimensions on patient satisfaction is studied to understand how those factors relate to the patients’ expectation and perception. In this qualitative case study, semi-structured interviews were conducted in 14 students and 4 staff whom visited UMPHC and the results were analysed through thematic analysis. In this research, seven themes (Responsiveness, Reliability, Assurance, Empathy, Tangible, Technical Quality and Elements that could improve PS) are created which further branches to a total of 21 sub themes. Location of UMPHC or accessibility to the services, extended services (dental), staff’s attitude and communication skill, consistency in following the SOPs, waiting time, technical quality as well as health education were amongst the most important factors affecting patient satisfaction. The UMPHC health managers should focus on the above aspects and implement appropriate management decisions to improve patient satisfaction.